Characteristics of lasers based on binary vanadate and orthoborate single crystals with disordered structure - Kosmyna, M.B.; Nazarenko, B.P.; Radchenko, I.O.; Shekhovtsov, A.N. (Functional Materials, 2015)
Characteristics of lasers based on the binary orthovanadates Ca₁₀Li(VO₄)₇:Nd, Ca₉La(VO₄)₇:Nd and the orthoborates Ca₃RE₂(BO₃)₄:Nd (RE = Y, Gd) crystals with disordered structure were investigated. For Ca₃Y₂(BO₃)₄:Nd crystals laser oscillations was observed for the first time. The obtained slope efficiencies of vanadate-based lasers are comparable with the one of the lamp-pumped laser based on commercial Y₃Al₅O₁₂:Nd crystal. The optical breakdown threshold of binary vanadate crystals is higher than that of the orthoborate crystals. For Ca₁₀Li(VO₄)₇:Nd and Ca₉La(VO₄)₇:Nd crystals the values of optical breakdown threshold are approximately the same - 80 J/cm². The optical breakdown thresholds of Ca₃Y₂(BO₃)₄:Nd and Ca₃Gd₂(BO₃)₄:Nd crystals is approximately twice as low.